Structure and growth mechanism of CuO plates obtained by microwave-hydrothermal without surfactants - Moura, A. P.; Cavalcante, L. S. [UNESP]; Sczancoski, J. C.; Stroppa, D. G.; Paris, E. C.; Ramirez, A. J.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2010)
CuO plates were obtained by microwave-hydrothermal processing at 130 C for 30 min without any surfactant. X-ray diffraction, Rietveld refinement and selected area electron diffraction showed that the CuO plates present a monoclinic structure without secondary phases. The nitrogen adsorption isotherm measurements revealed a specific surface area of approximately 30 m(2)/g. Field-emission gun scanning electron microscopy and transmission electron microscope micrographs indicated that the growth process of these plates was through Ostwald ripening and aggregation of plates surface by Van der Waals forces along to the two [100] and [010] directions. (C) 2009 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: CuO; Plates; Rietveld refinement; Microscopy; Crystal growth